(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
The article presents the results of checking the system of internal and financial control of environmental aspects of the activities of manufacturing enterprises. The main problems associated with the formation, removal and disposal of solid household and industrial waste are described. Brief conclusions are presented based on the results of the study of scientific literature and regulatory documentation on the stated topic. The measures taken to reduce and control the export of solid domestic and industrial waste are described. The methods of economic regulation of the activities of enterprises in the field of environmental protection are presented, the requirements for organizing the accounting of environmental payments, and the formation of statistical reporting are described. The author’s methodology for the preparation of an environmental policy for the environmental aspects of the activities of industrial enterprises is presented on the example of transport organizations involved in the removal of solid domestic and industrial waste